Comparison of Two Technical Variants for Virtual Training - David KRAKORA; Petr HOREJSI; Jan KUBR; Konstantin NOVIKOV (Communications of International Proceedings, 2021)
This article deals with the comparison of two technologies for use in virtual training. The aim is to compare two technologies that can be used for training and coaching new employees with a focus on use in industrial companies. A pilot study was created for an objective comparison. A total of 20 volunteers who took part in the measurement were divided into two groups depending on the technology they used (HTC Vive and Leap Motion). HTC is a headset that uses drivers to interact. LM focuses on hand tracking and gesture control. Both technologies were implemented in the same VR environment and their use for VT was investigated. The time taken for each tester to assemble their model was measured. For a more effective comparison, a questionnaire was created, with graded and open questions. Basic statistical values ​​were determined and compared. The results showed that the HTC variant is more efficient for virtual training. Compared to the LM controller, this headset is faster, more accurate, more intuitive and more efficient for interacting with objects. LM is an interesting tool that offers control by hand tracking, but from our point of view it is a pilot project that still needs to be fine-tuned.
Keywords: Virtual reality; Virtual training; Comparison of VR technologies; pilot study-4 keywords